2018
DOI: 10.1111/1365-2745.13092
|View full text |Cite
|
Sign up to set email alerts
|

A hyper‐arid environment shapes an inverse pattern of the fast–slow plant economics spectrum for above‐, but not below‐ground resource acquisition strategies

Abstract: 1. The fast-slow plant economics spectrum predicts that because of evolutionary and biophysical constraints, different plant organs must be coordinated to converge in a unique ecological strategy within a continuum that shifts from fast to slow resource acquisition and conservation. Therefore, along a gradient of aridity, taxa with different strategies will be expected to be successful because selection pressures for slow resource acquisition become stronger as the environment becomes drier. In extremely arid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 78 publications
12
53
2
1
Order By: Relevance
“…We observed negative correlations between wood and leaf traits in both evergreen and deciduous species. Our results were similar to other studies that showed some degree of coordination between leaf and stem traits [46]. The leaf traits showed a negative relationship with wood density, which indicates that fast resource use by leaves is accompanied by fast water conduction by the stem.…”
Section: Pairwise Trait Correlationsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed negative correlations between wood and leaf traits in both evergreen and deciduous species. Our results were similar to other studies that showed some degree of coordination between leaf and stem traits [46]. The leaf traits showed a negative relationship with wood density, which indicates that fast resource use by leaves is accompanied by fast water conduction by the stem.…”
Section: Pairwise Trait Correlationsupporting
confidence: 91%
“…The leaf traits showed a negative relationship with wood density, which indicates that fast resource use by leaves is accompanied by fast water conduction by the stem. Therefore, above-ground traits respond concordantly to the same habitat stresses promoting rapid resource acquisition [46]. The level of coordination between wood and leaf traits can be multidimensional, meaning that certain wood traits coordinate with leaf traits while others vary independently in determining resource acquisition strategies [47].…”
Section: Pairwise Trait Correlationmentioning
confidence: 99%
“…Such functional changes at community level were also determined by the covariation between intraspecific trait variability and species turnover, which varied in sign depending on the trait considered. Most studies centered on plants (e.g., Lepš et al 2011, Kumordzi et al 2014, Carvajal et al 2018, Liu et al 2019) and the few including lichens (Roos et al 2019), found that species turnover and intraspecific trait variability tend to positively covary, whereas here we found the opposite; that is, twice as many cases showed a negative covariation (Fig. 2).…”
Section: Discussioncontrasting
confidence: 43%
“…S4). The observed changes could be related to a physiological limit for the existence of stress-tolerant strategies and evergreen vegetation at aridity levels > 0.8, as this vegetation is replaced by stress-avoidant summer deciduous shrub species that may benefit most from the sparse and unpredictable rain events characterizing these environments (21,29) (Fig. S6D).…”
Section: Main Textmentioning
confidence: 99%